Meningoencephalitis of listeriosis etiology. A case from practice - Z. G. Tagirova; Zh. B. Ponezheva; V. V. Makashova; А. D. Muzyka; S. V. Krasnova (Лечащий Врач, 2023)
Background. Listeriosis is a widespread natural focal infectious disease in humans and animals, characterized by a variety of sources of the causative agent of infection, as well as variability in clinical course and outcomes. The clinical manifestations of the disease are diverse, the most dangerous are the generalized forms – septic and nervous (meningitis, meningoencephalitis), which often develop with generalization of the gastrointestinal form. Constant monitoring allows you to monitor the emergence of new foci of the disease and their spread in the countries of the world, including Russia. Given the emergence of listeriosis outbreaks around the world and the significant severity of the disease, the World Health Organization is actively developing preventive measures.   Objective. To draw the attention of practitioners of various profiles to the nervous form of listeriosis, which occurs in the form of meningitis and/or meningoencephalitis.   Materials and methods. The article presents a clinical case with a favorable outcome, describing damage to the central nervous system due to listeriosis in a 67-year-old patient who was admitted to Infectious Diseases Clinical Hospital No. 2 in Moscow in serious condition. The diagnosis of listeria meningoencephalitis was established on the basis of epidemiological, clinical, laboratory and instrumental data; when examining the cerebrospinal fluid using PCR, Listeria monocytogenes DNA was detected. Damage to the central nervous system with the development of meningoencephalitis was caused first by listeria, and then by the addition of secondary flora (Streptococcus species group G, detected by culture of cerebrospinal fluid). After the treatment, the patient was discharged in satisfactory condition with subsequent follow-up by an infectious disease specialist and a neurologist.   Conclusion. The clinical case demonstrates the difficulties in diagnosis and draws the attention of practitioners to the need for caution against listeriosis in the differential diagnosis of meningitis and meningoencephalitis of various etiologies.